Effectiveness of continuous epidural analgesia by bupivacaine 0.1% combined with fentanyl for pain attenuation during labor at Hue Central Hospital - Xuan, Nguyen Thanh; Dung, Le Van; Hau, Nguyen Trung; Hien, Nguyen Viet Quang; Quang, Nguyen Thanh; Nam, Nguyen Ich Hai; Loan, Nguyen Thi Thanh; Hang, Pham Thi Diem; Khoi, Le Viet Nguyen; Tuan, Bui Anh; và c.s. (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Introduction: Epidural analgesia was an extremely effective and popular treatment for labor pain. This study aimed to assess the effectiveness and safety of combinational use of bupivacaine 0.1% and fentanyl in epidural anesthesia for pain relief during labor. Methods: A cross-sectional descriptive study was conducted on 270 parturients who required epidural anesthesia for pain relief during labor. All parturients received 06ml epidural solution of bupivacaine 0.1% with fentanyl (30μg). After 10 minutes, continuous epidural infusion (CEI) at 6 ml/h with bupivacaine 0.1% + fentanyl (2µg/ml). Extra boluses of 6ml solution of (bupivacaine + 0.1% fentanyl (2µg/ml) when VAS (Visual Analog Scale) score >6 points. Measured variables included total bolus requests, pain Visual Analog Scale (VAS), modified Bromage scores, labor duration, delivery outcome, and maternal satisfaction after delivery. Results: The average analgesia induction was 4.32 ± 0.58 minutes. VAS score ≤ 3 points: 88.52% of parturients, VAS score = 3-6 points: 8.52% of parturients (1 rescued bolus) and VAS score> 6 points 2.96% of parturients (2 rescued bolus). There were (208/270) 77.04% with normal labor. The average labor pain relief time was 161.98 ± 46.58 minutes. Side effects were as follows: Feeling numb in the leg (but still able to move): 8.15%; transient chills: 3.33%; nausea: 2.96%, itching: 1.85%. There were no cases of headache, hypotension, arrhythmia, respiratory failure and dural puncture. The average Apgar score at the 1st minute was 8.35 ± 0.24 and at the 5th minute was 8.79 ± 0.07, without cases of asphyxia. Regarding maternal satisfaction, very satisfied and satisfied levelsoccupied 74.04% and 25.96%, respectively. Conclusion: In our study, continuous epidural analgesia by combinational use of bupivacaine 0.1% and fentanyl(2µg/ml) provided effective labor pain relief, hemodynamic stability, and normal neonatal outcomes.